(untitled) (Journal of the College of Basic Education, 2023)
This study investigates possible change that occurs in the form of variants and inclusions in the constructions of some English idioms. Section One of this research paper explores definitions, types and distinctive features of idioms while Section Two provides a grammatical classification of lexical and functional subcategories of words that may occur in idioms as variants and inclusions. Section Three, on the other hand, introduces the analytic side of the study where 250 idioms are surveyed to diagnose examples of idioms that allow change of variants and inclusions. In This section, the researcher classifies and tabulates variants and inclusions into lexical and functional categories and subcategories in terms of frequency and percentage of occurrence. The paper ends up with the findings and conclusions of the study which provide a better insight into this realm of English Language study.